Penerapan Model Problem Based Learning Berbasis STEM untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik pada Materi Fluida Statis - Safina Amanda Putri; Hera Novia; Irma Rahma Suwarma (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to determine the improvement in students' cognitive learning outcomes, the implementation of learning, and student responses to the application of the STEM-based Problem-Based Learning model to Static Fluids. This study used a quantitative method with a pre-experimental research type and a One Group Pretest-Posttest Design. The study was conducted on 35 11th-grade students at a public high school in Cimahi City. The instruments used included a 15-question cognitive ability test, a learning implementation observation sheet, and a student response questionnaire. Improvements in each indicator of student cognitive learning outcomes were analyzed using the N-Gain test. The results showed that the average pre-test score of 65 increased to 87 in the post-test, with an N-Gain value of 0.61, which is categorized as moderate. The implementation of learning at each meeting reached 100% and was categorized as very good. Student responses to the implementation of the learning model also showed excellent results, with an average percentage of 87.04%, including motivation (90.00%), interest (86.99%), and satisfaction (84.14%). Based on these results, it can be concluded that the implementation of the STEM-based Problem-Based Learning model is effective in improving students' cognitive learning outcomes in Static Fluids.